ASUHAN KEPERAWATAN MASALAH PSIKOSOSIAL KECEMASAN PADA TN.S DENGAN STROKE DI KELURAHAN LIMO KOTA DEPOK - Edwina Retha Maharani (2023)
Background: Stroke or cerebrovascular injury, namely loss of brain function caused by disruption of blood supply to parts of the brain. This loss of brain function can occur suddenly, progressively and quickly. Anxiety is a feeling of fear, worry, and unrest accompanied by feelings of discomfort from the individual that can affect the individual's behavior. This research was conducted to understand the concept of nursing care for Mr. S who experienced psychosocial anxiety problems for Mr. S with a stroke in Kelurahan Limo . Method: This scientific paper uses the case study method. Research Results: In this case study, anxiety and stroke nursing problems were found where relaxation techniques such as deep breathing relaxation, PMR activities and 5 finger hypnosis were carried out to help reduce anxiety in stroke patients. Conclusion: The application of nursing care to Tn.S with psychosocial problems of anxiety with stroke achieves the expected results, where the patient is cooperative during the action.